Phytochemical Screening and Cytotoxic Activity in Chromolaena odorata (L.) R.M. King & H. Rob. Leaf and Root Extracts by Brine Shrimp Lethality Assay - Thapa, Chandra Bahadur; Thapa, Barsha; Marasini, Sanjay (Butwal Campus Journal, 2025)
Chromolaena odorata (L.) R.M. King & H. Rob., a rapidly expanding invasive plant, is traditionally used in ethnomedicine for wound healing, antibacterial, and anti-inflammatory purposes. This study analyzed the methanolic and aqueous extracts of the leaf and root of C. odorata qualitatively for major secondary metabolites and tested for cytotoxicity against Artemia salina nauplii using the Brine Shrimp Lethality Assay (BSLA). Phytochemical screening results showed that methanol and aqueous extracts comprised tannins, terpenoids, alkaloids, flavonoids, and saponins. The aqueous extract of roots showed the maximum cytotoxic activity on the Brine Shrimp nauplii with Lethal Concentration 50 (LC₅₀)=62.61 µg/mL, indicating the presence of potential bioactive or cytotoxic compounds. Furthermore, it was found that root extracts were more effective at cytotoxicity than leaf extracts and that both leaf and root aqueous extracts were more cytotoxic to nauplii than the methanolic extracts. The findings suggest that C. odorata contains bioactive compounds with potential cytotoxic activities, warranting further investigation for anticancer activities and identification and characterization of the bioactive compounds.